Malawi : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
In recent times, the Government of Malawi has undertaken various initiatives to strengthen the country's financial accountability framework. These include the following: A Medium-Term Expenditure Framework (MTEF) introduced progressively since 1995 to develop a strategic approach to budgeting over the medium-term, to improve resource allocations in accordance with emerging poverty reduction priorities, and to integrate the investment and recurrent sides of the dual budget; A cash budget system introduced in 1996 as a temporary measure to increase fiscal discipline and which remains in place as the central tool for budget implementation. An Integrated Financial Management Information System (IFMIS) project initiated in 1996 with the objectives of providing timely and accurate financial information; providing a standardized integrated financial management reporting system for the Government of Malawi at various operational levels; providing the Accountant General with a Government-wide upgraded computerized accounting system; and improving and strengthening financial control; A review of the Finance and Audit Act, which sought to improve the legal and regulatory framework for financial management in the public sector. The review also sought to provide for the independence of the Auditor General; A development of the system of Local Government guided by a comprehensive Decentralization Implementation Plan, jointly appraised by the Government of Malawi and the donors in August 2000. In spite of the foregoing, a lot more needed to be done and a number of prioritized recommendations are highlighted in the Development Action Plan.